State space controller of SLCC and design analysis with MPPT approaches - Natarajan, Jeyaprakash; Manoharan, Nivethitha Devi; Murugan, Mohanasanthosh; Lokeshwar Reddy, Karnati Venkata; Sudhakar, Thirumalaivasal Devanathan (Institute of Advanced Engineering and Science, 2025)
Power systems with standalone properties like remote unit telecommunication network requires high negative DC supply voltage. In such remote places, solar photovoltaic (PV) are used to generate power. Maximum power point tracking techniques (MPPT) gives unregulated voltage from solar panel. This unregulated voltage is converted into regulated voltage by providing proper pulse width modulation (PWM) signal to self-lift cuk converter (SLCC). In comparison with classic cuk converter, SLCC reduces load voltage and load current ripples. This paper focuses on state space controller design and implementation of SLCC used in MPPT based PV system. The switching pulse of SLCC can be generated by perturb and observe (P&O), incremental conductance (IC) and also using fuzzy control. The simulation of SLCC has been performed using MATLAB/Simulink and its specifications in time domain has been compared.